KESIAPAN SEKOLAH DALAM PERENCANAAN PEMBELAJARAN PENJAS BAGI SISWA TUNARUNGU DI SEKOLAH LUAR BIASA DALAM MENGHADAPI PANDEMI COVID 19 - Hayat , Amrul (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
The Aim of research is knowing how readiness of school in lesson plan for deaf students in schools is outstanding in the face of covid 19. This research is a type of qualitative descriptive research, which illustrates how school readiness in learning planning for deaf students in schools is outstanding in the face of covid- 19 pandemics. The subjects in the study were principals and physical education teachers. The data collection techniques used in this study are observation, interview and documentation. The data analysis techniques used in this study are data reduction, data display and data verification. The results showed that the school's readiness in planning the learning for deaf students in the school was outstanding in the face of covid-19 pandemic in terms of preparation was good enough, while in the implementation and evaluation stage was relatively poor due to the onsanion of out-of-school learning by not doing face-to-face when teaching. In addition, the role of physical education teachers has not been able to performwell when in planning physical education learning during the covid-19 pandemic.